2022
DOI: 10.3389/fpsyg.2022.912368
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Affective Responses Between Time Efficient and Traditional Resistance Training

Abstract: The aim of the study was to compare the acute effects of traditional resistance training and superset training on training duration, training volume and different perceptive measures. Twenty-nine resistance-trained participants (27 ± 7 years, 173 ± 9 cm, and 70 ± 14 kg) performed a whole-body workout (i) traditionally and (ii) as supersets of exercises targeting different muscle groups, in a randomized-crossover design. Each session was separated by 4–7 days, and consisted of eight exercises and three sets to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Our finding is in line with the results from a previous study from our lab comparing traditional and superset resistance training among resistance-trained (Andersen et al, 2022 ). The study indicated that the more strenuous superset session led to higher discomfort and effort among participants, but also tended to be more pleasurable (Andersen et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our finding is in line with the results from a previous study from our lab comparing traditional and superset resistance training among resistance-trained (Andersen et al, 2022 ). The study indicated that the more strenuous superset session led to higher discomfort and effort among participants, but also tended to be more pleasurable (Andersen et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…Since all sessions were perceived as similarly exertive, it seems likely that they would be rated as similarly good/bad on the sPDF scale. Notably, it has been reported that the feeling of working hard is important for the preference of a workout 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic stress-related mechanisms might also partially explain the participants’ responses for feelings of pleasure/displeasure. Previous studies (Andersen et al, 2022; Gjovaag et al, 2016; Ribeiro et al, 2019) showed that lighter load conditions, compared to higher load conditions, promoted more unpleasant responses and higher session RPE and cardiovascular responses. These metabolic responses could also lead to distinct degrees of peripheral fatigue in DS training compared to other ResisT schemes.…”
Section: Discussionmentioning
confidence: 88%
“…Psychophysiological responses measured by the rating of perceived exertion (RPE) and feelings of pleasure/displeasure (FPD) are useful tools for planning and monitoring ResisT programs (Andersen et al, 2022; Scott et al, 2016). These responses can help coaches and practitioners monitor the dose–response relationship between training methods and desired training effects (Scott et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation